Early Cretaceous Terrestrial Milankovitch Cycles in the Luanping Basin, North China and Time Constraints on Early Stage Jehol Biota Evolution - Liu, Wei; Wu, Huaichun; Hinnov, Linda A.; Xi, Dangpeng; He, Huaiyu; Zhang, Shihong; Yang, Tianshui (Frontiers in Earth Science, 2020)
This research analyzes the cyclostratigraphy of the lacustrine Dabeigou Formation (DBG) of early Jehol Biota age (~130-135 Ma) in the Luanping Basin, northern China. A high-resolution (2 cm interval), 117.82-meter-long magnetic susceptibility (MS) stratigraphic series was measured along the Yushuxia section. MS is positively correlated with thorium, potassium and uranium concentrations associated with gamma ray intensity, and represents a proxy for detrital influx to the Luanping Basin. Power spectral analysis identifies a hierarchy of sedimentary cycles with wavelengths of 16.38 m, 5.85-3.28 m, 1.88-1.33 m and 0.98-0.7 m, which are interpreted to represent Earth’s orbital eccentricity, obliquity and precession index cycles. Objective testing of the MS series supports the interpretation of Milankovitch cycles, indicating an average sedimentation rate of 4.642 cm/kyr to 4.723 cm/kyr. A floating astronomical time scale with a duration of 2478 kyr is established from interpreted 405 kyr long orbital eccentricity cycles along the MS series. The 405-kyr tuned DBG MS time series closely matches the predicted orbital eccentricity of the La2004 astronomical solution from 130.787 Ma to 133.265 Ma, providing independent temporal constraints on early stage Jehol Biota evolution. Finally, this estimated time interval for the DBG MS time series indicates that it occurred entirely within the Weissert Event.